2002
DOI: 10.1023/a:1015497629971
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: People with high functioning autism (HFA) and Asperger syndrome (AS) have deficits in theory of mind (ToM). Traditional ToM tasks are not sensitive enough to measure ToM deficits in adults, so more subtle ToM tests are needed. One adult level test, the Reading the Mind in the Eyes test has shown that AS and HFA subjects have measurable deficits in the ability to make ToM inferences. Here we introduce a test that extends the above task into the auditory domain and that can be used with adults with IQ Scores in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
63
1
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 326 publications
(69 citation statements)
references
References 26 publications
3
63
1
1
Order By: Relevance
“…This factor must be taken into consideration when analysing the temporal effects of a stimulus on SI. There appears to be a high degree of consistency in the movement of manganese through the CNS as evidenced by the use of manganese uptake as a reliable marker of normal tissue, compared to differential uptake of Mn 2+ in pathological conditions associated with tumours or ischemia [92]. Further understanding of the diffusion mechanics of manganese into regions of the hypothalamus should provide a background onto which the temporal effects of applied stimuli can be determined.…”
Section: Analysis Of Temporal Changes In the Memri Signalmentioning
confidence: 99%
“…This factor must be taken into consideration when analysing the temporal effects of a stimulus on SI. There appears to be a high degree of consistency in the movement of manganese through the CNS as evidenced by the use of manganese uptake as a reliable marker of normal tissue, compared to differential uptake of Mn 2+ in pathological conditions associated with tumours or ischemia [92]. Further understanding of the diffusion mechanics of manganese into regions of the hypothalamus should provide a background onto which the temporal effects of applied stimuli can be determined.…”
Section: Analysis Of Temporal Changes In the Memri Signalmentioning
confidence: 99%
“…The group analysis showed significant differences in the prosodic performance of children with HFA compared to typically developing peers, and suggested that language abilities were strongly correlated with prosody. The results are consistent with the findings of studies on other languages, in which children with HFA performed significantly poorer than controls on at least one prosodic task (e.g., Peppé el al., 2007;Rutherford, Baron-Cohen, & Wheelwright, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Most of the studies in this area have focused primarily on the perception of pragmatic/affective prosody (Chevallier, Noveck, Happé, & Wilson, 2011;Globerson et al, 2014;Golan, Baron-Cohen, & Hill, 2006;Golan, Baron-Cohen, Hill, & Rutherford, 2007;Grossman, Bemis, Plesa Skwerer, & Tager-Flusberg, 2010;Heikkinen et al, 2010;Järvinen-Pasley, Wallace, Ramus, Happé, & Heaton, 2008b;Jones et al, 2011;Kleinman, Marciano, & Ault, 2001;Lindner & Rosén, 2006;Peppé, McCann, Gibbon, O'Hare & Rutherford, 2007;Rutherford, Baron-Cohen, & Wheelwright, 2002). Several of these studies using complex vocal expressions (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…tasks that demand enhanced cognitive load), reported findings for atypical perception of pragmatic and affective prosodic cues in individuals with ASD (e.g., Chevallier et al, 2011;Golan et al, 2006Golan et al, , 2007Kleinman et al, 2001;Rutherford et al, 2002). In contrast, the processing of basic voice expressions and vocalizations (e.g., laughing-happy, crying-sad) appear to be intact in children, adolescents and adults with ASD (Grossman et al, 2010;Heikkinen et al, 2010;Jones et al, 2011), although some studies failed to replicate these findings (Lindner & Rosén, 2006;Mazefsky & Oswald, 2007;Philip et al, 2010).…”
Section: Introductionmentioning
confidence: 99%